Prevalence of feline calicivirus in cats with odontoclastic resorptive lesions and chronic gingivostomatitis. (April 2017) - Thomas, Sheeba; Lappin, David F.; Spears, Julie; Bennett, David; Nile, Christopher; Riggio, Marcello P.
Abstract: Feline odontoclastic resorptive lesion (FORL) and feline chronic gingivostomatitis (FCGS) are two of the most common diseases of the feline oral cavity. While evidence is emerging that FCGS is caused by gingival inflammation initiated and perpetuated by the oral microbiota, little is known in this regard for FORL. Feline calicivirus (FCV) has been associated with the presence of FCGS and is thought to play a role in the initiation of this disease. In this study, the incidence of FCV was investigated in cats with FORL and FCGS, and compared to unaffected controls. FCV was detected by viral culture. The incidence of FCV was as follows: 6 (24.0%) of 24 control cats, 9 (22.5%) of 40 cats with FORL and 15 (60.0%) of 25 cats with FCGS were positive for FCV. There was a significant difference in FCV incidence between all the groups ( p  = 0.003) but none between the control group and the FORL group. However, significant differences were observed in the incidence of FCV between control and FCGS ( p  = 0.010) and between FORL and FCGS ( p  = 0.006). It is concluded that although FCV may be associated with FCGS, it appears unlikely to play a role in FORL. Highlights: First study investigating the relationship between FORL and FCV Presence of FCV is significantly associated with FCGS. Presence of FCV is not associated with FORL. FCV is unlikely to play a role in the aetiopathogenesis of FORL.